Scientific Instruments on the move in the North American Magnetic Survey, 1843-1844 - Goodman, Matthew (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2016)
In 1843-4, John Henry Lefroy conducted a geomagnetic survey of Hudson’s Bay Company territory in British North America. Lefroy and his instruments, guided by French Canadian voyageurs and Indigenous guides moved within the HBC network of forts and outposts. This paper complements and extends historical accounts of Lefroy’s survey by examining how, and how well, Lefroy’s instruments moved on this extensive survey. The recent material turn in the history and historical geography of science provides the framework for a closer reading of the spatial biographies of several of Lefroy’s instruments. Focusing on their varying states of disrepair—and solutions to repair them—this paper not only recaptures the materiality of these instruments, but adds to our understanding of repair and maintenance in the history of survey science. Looking at instruments as objects to be carried and managed also helps illuminate the overlooked role of Indigenous and French Canadian voyageurs in scientific expeditions.